Fetal Biparietal Diameter and Abdominal Circumference Ratio in Bangladesh (Bangladesh Medical Journal, 2010)
This study was conducted to determine fetal biparietal diameter and abdominal circumference ratio in Bangladesh. There is still no table of this ratio in our country. A prospective, cross-sectional study was conducted on well dated, singleton fetuses of healthy pregnant women. One table and two graphs were prepared by fitting Polynomial regression model. Percentiles, mean and two standard deviations were derived of the ratio. Fetal charts of the raw data with superimposed fitted curves were constructed. The model showed a good fit to the data of 1223 subjects. It covered 95% of the population and gave 3rd, 10th, 50th, 90th and 97th percentiles. This chart can be useful for accurate assessment of fetal biparietal diameter and abdominal circumference ratio to determine the type of fetal growth abnormality, symmetrical or asymmetrical. This is the first time that this ratio has been studied in Bangladesh. Key words: Biparietal diameter; abdominal circumference. DOI: 10.3329/bmj.v39i1.6229 Bangladesh Medical Journal 2010; 39(1): 24-27